?DETERMINATION OF SORPTION-IsOTHERMS IN FOOD (Biological Sciences - PJSIR, 1998)
Water activity (a) in food at known moisture content can be determined by instruments or determination of moisture content and equilibration against saturated salt solution in conventional desiccator. However, in these methods equilibration takes a long time, depending upon food composition. In this work a simple and inexpensive method has been developed to obtain sorption-isotherm in short time for determining a w of a food. A small plastic cup was chosen (7crn/5cm) as a vessel. A weighed food in small glass beaker was rested on plastic stand in the vessel containing saturated salt solution 1/3 of its volume. The vessel was cap-closed and airtight. This technique was used for determination of a w of dehydrated banana chips and equilibration was reached in 2 days which otherwise required 20 days for the conventional desiccator.